Impulsive stimulated Raman scattering of molecular vibrations using nonlinear pulse shaping - Bartels, R. A., author; Murnane, M. M., author; Backus, S., author; Kapteyn, H. C., author; Elsevier Science B. V., publisher (Colorado State University. Libraries, 2003)
We demonstrate the excitation of a molecular vibrational coherence via impulsive stimulated Raman scattering (ISRS) by using a pump pulse longer than the vibrational period of the excited mode. By making use of the reshaping of the pump pulse during nonlinear propagation, a Raman vibrational coherence can be excited via ISRS with a pump pulse incapable of such excitation at the input of the medium.